PENERAPAN STRATEGI PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR (SPPKB) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV MIN BAGAN SIAPI-API - Farida Farida; Otang Kurniaman; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is to study the IPS is still low, there are still many students who do not understand the basic concepts and tend to memorize examples. It was seen from the percentage of test scores of students who reached the KKM (Minimum completeness criteria) in the fourth grade MIN Bagan Siapi-fire is 37.50% of the 16 students with an average value is 57.86. The KKM specified school is 70.. This research was conducted in two cycles, the first cycle consisted of three meetings with one daily tests and the second cycle also consists of three meetings with one daily tests. The data in this study is the observation sheet teacher activity, student activity observation sheet and test daily tests. With the implementation of Learning Strategies Enhanced Thinking Skills (SPPKB) can improve learning outcomes IPS Grade IV MIN Bagan Siapi-fire from a base score 58.13 and increased in the first cycle with an average amounted to 77.50 with the percentage increase of the base score to UHI sebesar33,33%. Basic score to UH II with an average of 58.13 into 87.19 with an increasing percentage of the base score to UH II 50.00%. Activities teachers in implementing the learning increases at each meeting of the average teacher activity score 71.87% in the first meeting of the first cycle increased to 79.16% at the second meeting of the cycle I. While the second cycle of the average teacher activity score 84.37 % in the first meeting increased to 93.75% with very good category at the second meeting. Learning activities of students in learning has increased at each meeting. At the first meeting of the first cycle and 71.87% in the second meeting increased to 78.12%. While on the second cycle an average 84.37% increase to 93.75%. Based on the results of this study concluded that the application of IPS learning SPPKB in the fourth grade students MIN Bagan Siapi-fire acceptable.Key Words: Learning Strategies for increasing the capacity of Thinking (SPPKB), IPS Learning Outcomes